Strongly Primary Submodules - Naoum, A.; Hadi, Inaam (Iraqi Journal of Science, 2025)
Let M be an R-module, where R is an integral domain with quotient field K .In this paper we introduce the concept of strongly primary submodule, where a submodule N of M is called strongly primary, it whenever r& K.xe M.rs EN Implies xeN or re(N:M) for some nez.. We study this concept and give some of its properties.